Vídeos didáticos do youtube: um estudo sobre a utilização de vídeos nas aulas de Língua Portuguesa no 9º ano do Colégio Militar Tiradentes I - SOEIRO, Jermany Gomes (2021)
The present study deals with Didactic Videos on YouTube: A study on the didactic use of videos in Portuguese Language classes in the 9th grade of Colégio Militar Tiradentes I. The general objective of the research was outlined: to investigate how Portuguese Language teachers use the didactic videos hosted on YouTube in Portuguese language classes in the 9th grade of Colégio Militar Tiradentes. The issue was drawn from the following question: How are didactic videos used in Portuguese language classes in the 9th grade of Elementary School at Colégio Militar Tiradentes I? Thus, the following bibliographical references were used: Bottentuit Junior (2017), Daniel (2020), Fava (2018), Ferreira and Costa (2020), Garces (2010), Kenski (2012), Moran (2015), Moran, Masetto and Behrens (2013), Puhler and Matsuda (2020), Souza, Simon and Fialho (2015), Tardif and Raymond (2000), Yin (2001), among others. The methodology used was the case study, with a qualitative approach and exploratory nature. The data collection instruments used were online questionnaires carried out by the digital platform Google Forms. For data analysis and interpretation, graphs were used. The product of the research was a Didactic Manual in digital format for Portuguese language teachers in the 9th grade, but care must be taken with the quality of the videos in relation to image and sound, as well as the way in which this didactic strategy is designed with these chosen videos.